Mediator Non-Hakim: Geliat KUA Dalam Menyelesaikan Permasalahan Wali Nikah di Kota Langsa - Muhazir, Muhazir; Putra, Nanda Herijal; Sufrizal, Sufrizal (Program Studi Hukum Keluarga Islam UIM Pamekasan, 2024)
Although the guardian plays a crucial function in marriage, there are numerous issues that can occur when the guardian declines to act in that capacity. Their children are left with a conundrum by this. The study will examine how the KUA can settle guardianship disputes in Langsa City without escalating disputes or requiring an application to be made to the religious court. The empirical studies that were used to develop this research used a normative sociological methodology. With this method, the empirical features of how mediation can be carried out by non-judge mediators are taken into consideration in addition to the normative analysis. This study contends that the KUA plays a significant role in settling the issue of marriage guardians, and that the way selected can prevent lengthy conflict between children and dads. Following mediation, taukil wali replaces wali adhal. This approach is seen to be quite effective because it doesn't create any disturbance and the marriage still happens, therefore it eliminates the possibility that the prospective bride and groom may flee.